Perlindungan Hukum Perawat Dari Kekerasan Pasien Dan Atau Keluarganya - Tribakti, Ichlas; Wijayanti, Edy; Putra, Yusak Andri Ende (Barongko: Jurnal Ilmu Kesehatan, 2024)
Legal protection for nurses is an important aspect of nursing practice aimed at ensuring the safety and security of nurses while carrying out their professional duties. Legal protection for nurses is crucial in this situation. With the existence of regulations governing the rights and obligations of nurses, it is hoped that it can provide assurance that nurses are protected from acts of violence or threats that may arise while performing their duties. Law Number 36 of 2014 on Health Workers and Law Number 17 of 2023 on Health provide a clear legal framework for this protection. The authority of nurses to perform medical actions and nursing care must be balanced with adequate legal protection. When nurses face potentially dangerous situations, they must feel safe to carry out their duties without fear of negative repercussions from patients or their families. Therefore, it is important to create a safe working environment where nurses can perform their roles with professionalism and without threats. Research Objective Juridical Normative with a descriptive research method. Results The results of this study conclude that the legal relationship established between nurses and patients has implications for legal protection from ethical aspects and legal responsibilities in each institution, such as hospitals. While the regulations governing this are clear, their application in the field is still minimal due to the lack of legal awareness among nurses regarding protection from violence that may be perpetrated by patients or their families. Increasing legal understanding among nurses is essential to optimize protection and enhance the quality of health services.